Faktor-Faktor Yang Berhubungan dengan Perilaku Pencarian Pelayanan Kesehatan (Health-Seeking Behavior) Terkait Tuberkulosis pada Masyarakat - Vita One Sari Sinambela; Helmi Suryani Nasution; Marta Butar Butar; M. Ridwan; Rd. Halim (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Health-seeking behavior in TB is needed to break the chain of transmission. In 2024, TB case notification in Jambi City did not reach the target of the 2030 TB Control Strategy. Seeking health services will increase case notification rates and break the chain of transmission. Methods: Quantitative with a cross-sectional approach conducted in the community of Mayang Mangurai Village with a minimum sample of 220. Questionnaire filling by direct interview. Respondents were selected using probability proportional to size (PPS). The questionnaire was filled in using the KoboCollect v2024.2.4 application and analyzed using STATA version 17, univariate and bivariate data analysis. Bivariate analysis was performed with chi-square. The study aimed to determine the factors associated with health-seeking behavior related to tuberculosis. Results: A total of 251 respondents answered the interview questions. Respondents who had poor behavior were 65.7%. There was no significant relationship between age, gender, education level, occupation, income, knowledge, and attitude with health-seeking behavior. Most people learned about TB for the first time through family, friends, neighbors, and coworkers. The most effective source of information for respondents was social media. Conclusion: None of the independent variables was statistically significantly associated with the dependent variable.